Interrogating the determinants of customers purchase of imported used cars in Nigeria - EWANLEN, Donald (EuroEconomica, 2023)
This study investigates the factors that influence customers’ purchase of imported used cars in Nigeria. The paper specifically sought to ascertain the extent of gender differences in customers’ perception of these factors. This study adopted a cross sectional survey research design. The population of study are the entire patrons of imported used cars market in Benin City, Edo state Nigeria. 400 copies of questionnaire were conveniently administered to respondents at the cars dealers’ shops in Sapele road Benin City. Out of which 300 were found useable. The data collected were analyzed using mean and standard deviation. An ANOVA test of difference was employed to test the formulated hypothesis at 5% level of significance. The results show that customers consider car mileage as the most important factor that influence purchase of imported used cars, while condition of car tires was considered least important. The study further reports significant gender difference in customers’ perception of the factors that influence purchase of imported used cars. This paper recommends that buyers of imported used cars should patronize dealers of high repute to avoid procuring stolen and salvaged cars. Key Words: Extrinsic cues, Intrinsic cues, Imported used cars, Nigeria.